The localised madrasas of Afghanistan: their political and governance entanglements - Choudhury, Nafay (Religion, state & society, 2017)
This paper focuses on the operation of madrasas in Afghanistan. While numerous projects, initiatives and studies have focused on education generally in Afghanistan, considerably less attention has been directed towards madrasas specifically. Part of the reason can be attributed to the unclear role they play in the wider efforts to provide education across the country and the difficulty of formally including them within the nation-building project. The claim of this paper is that madrasas in Afghanistan are by and large localised and community-driven. The localised nature of Afghan madrasas can be understood as the product of the political tensions throughout the country's history between a state marked by tenuous authority and dispersed communities closely observant of unwelcome state interference. Moreover, the government lacks the resources and reach to provide educational services in many rural areas, thereby tacitly relying on localised madrasa to provide a base level of education to much of the population. Understanding the entanglements between education, politics and authority is crucial for appreciating the unique space that madrasas inhabit within the country.